If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = lwh Solving 60 = hlw Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1hlw' to each side of the equation. 60 + -1hlw = hlw + -1hlw Combine like terms: hlw + -1hlw = 0 60 + -1hlw = 0 Add '-60' to each side of the equation. 60 + -60 + -1hlw = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -1hlw = 0 + -60 -1hlw = 0 + -60 Combine like terms: 0 + -60 = -60 -1hlw = -60 Divide each side by '-1lw'. h = 60l-1w-1 Simplifying h = 60l-1w-1
| 0=320x-x^2 | | 4600-(100+3x)=0 | | 7+4(3x-5)=9-3(2x+1) | | W=4w | | 2000=225(x+3.5) | | 7-4(3x-5)=9-3(2x+1) | | 0=675x-16250-x^2 | | 9x^2+48x+140=0 | | 2x^2-13x+4.25=0 | | 360=2lw+2lh+2wh | | 7+4(3x-5)=9-3(2x-1) | | 3+2x=7x-47 | | 7-4(3x-5)=9-3(2x-1) | | 2x^2+10x=180 | | 14.2-d=9.2 | | 2.9(f+4)-1.22=16.18 | | -2.12(w+-4)=12.72 | | -4r^2+21r=r+13 | | 45=6x+3x+9 | | 140/u=28 | | 4x^2-1/16=0 | | 11(y-881)+234=806 | | R=8x^2+2x-9 | | 17+2= | | 4x^2-1/6=0 | | 6.7-j=6.8 | | 9x-3=6x+5 | | X^2+1=4+2x-x^2 | | M/5+(3m-6)/2=2m-6 | | 2.8(t-6)+1=9.4 | | 3(s+1.78)=11.67 | | 183-p=851 |